Polymorphisms of ATG5 Gene Are Associated with Autoimmune Thyroid Diseases, Especially Thyroid Eye Disease - Wen Wang; Zheng-yao Yu; Rong-hua Song; Shuang-tao He; Liang-feng Shi; Jin-an Zhang (Journal of Immunology Research)
Objective. To explore the association of ATG5 gene polymorphisms with autoimmune thyroid diseases (AITDs) including Hashimoto’s thyroiditis (HT) and Graves’ illness (GD) as well as their clinical features. Methods. rs6568431, rs548234, and rs6937876 were selected to investigate the correlation of single-nucleotide polymorphisms of ATG5 gene with AITDs. Their frequencies in 824 AITD patients, including 271 HT patients and 553 GD patients, and 764 healthy controls were tested using both ligase detection reaction and multiplex polymerase chain reaction. Results. Allele A frequency of rs6568431 in AITDs patients (p=0.016, OR=1.201, 95% CI=1.034−1.394) and allele G frequency of rs6937876 in AITDs patients (p=0.009, OR=1.223, 95% CI=1.052−1.422) and in GD patients (p=0.009, OR=1.247, 95% CI=1.056−1.473) were significantly higher than those in the healthy controls. The frequency of G allele (p=5.42E−18, OR=0.242, 95% CI=0.173−0.339) of rs6937876 was significantly higher in GD patients with ophthalmopathy. However, no relationship was found between family history, age onset, and the three SNPs. Conclusion. The study is the first to reveal the association between AITDs and ATG5 polymorphisms, and ATG5 gene is considered as a predisposing gene to AITDs, especially GDs.